Trotting Gait of a Quadruped Robot Based on the Time-Pose Control Method. (28th February 2013) - RunBin, Cai; YangZhen, Chen; WenQi, Hou; Jiang, Wang; HongXu, Ma
We present the Time-Pose control method for the trotting gait of a quadruped robot on flat ground and up a slope. The method, with brief control structure, real-time operation ability and high adaptability, divides quadruped robot control into gait control and pose control. Virtual leg and intuitive controllers are introduced to simplify the model and generate the trajectory of mass centre and location of supporting legs in gait control, while redundancy optimization is used for solving the inverse kinematics in pose control. The models both on flat ground and up a slope are fully analysed, and different kinds of optimization methods are compared using the manipulability measure in order to select the best option. Simulations are performed, which prove that the Time-Pose control method is realizable for these two kinds of environment.